Piezo-Enhanced Photocatalytic Activity of the Electrospun Fibrous Magnetic PVDF/BiFeO3 Membrane - Orudzhev, Farid; Sobola, Dinara; Ramazanov, Shikhgasan; Částková, Klára; Papež, Nikola; Selimov, Daud A; Abdurakhmanov, Magomed; Shuaibov, Abdulatip; Rabadanova, Alina; Gulakhmedov, Rashid; Holcman, Vladimír (Polymers, 2023)
Creating stimulus-sensitive smart catalysts capable of decomposing organic dyes with high efficiency is a critical task in ecology. Combining the advantages of photoactive piezoelectric nanomaterials and ferroelectric polymers can effectively solve this problem by collecting mechanical vibrations and light energy. Using the electrospinning method, we synthesized hybrid polymer-inorganic nanocomposite fiber membranes based on polyvinylidene fluoride (PVDF) and bismuth ferrite (BFO). The samples were studied by scanning electron microscope (SEM), Fourier-transform infrared spectroscopy (FTIR), total transmittance and diffuse reflectance, X-ray photoelectron spectroscopy (XPS), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), vibrating-sample magnetometer (VSM), and piezopotential measurements. It has been demonstrated that the addition of BFO leads to an increase in the proportion of the polar phase from 86.5% to 96.1% due to the surface ion-dipole interaction. It is shown that the composite exhibits anisotropy of magnetic properties depending on the orientation of the magnetic field. The results of piezo-photocatalytic experiments showed that under the combined action of ultrasonic treatment and irradiation with both visible and UV light, the reaction rate increased in comparison with photolysis, sonolysis, and piezocatalysis. Moreover, for PVDF/BFO, which does not exhibit photocatalytic activity, under the combined action of light and ultrasound, the reaction rate increases by about 3× under UV irradiation and by about 6× under visible light irradiation. This behavior is explained by the piezoelectric potential and the narrowing of the band gap of the composite due to mechanical stress caused by the ultrasound.
Keywords: piezo-photocatalysis; electrospinning; fibers; photocatalysis; smart materials; PVDF; piezocatalysis; BiFeO3